Cloning and expressing a highly functional and substrate specific farnesoic acid o‐methyltransferase from the Asian citrus psyllid (Diaphorina citri Kuwayama). Issue 1 (28th March 2015) - Van Ekert, Evelien; Shatters, Robert G.; Rougé, Pierre; Powell, Charles A.; Smagghe, Guy; Borovsky, Dov
Abstract : The Asian citrus psyllid, Diaphorina citri, transmits a phloem‐limited bacterium, Candidatus 'Liberibacter' asiaticus that causes citrus greening disease. Because juvenile hormone (JH) plays an important role in adult and nymphal development, we studied the final steps in JH biosynthesis in D. citri . A putative JH acid methyltransferase ortholog gene ( jmt D) and its cognate cDNA were identified by searching D. citri genome database. Expression analysis shows expression in all life stages. In adults, it is expressed in the head‐thorax, (containing the corpora allata), and the abdomen (containing ovaries and male accessory glands). A 3D protein model identified the catalytic groove with catalytically active amino acids and the S‐adenosyl methionine (SAM)‐binding loop. The cDNA was expressed in Escherichia coli cells and the purified enzyme showed high preference for farnesoic acid (FA) and homoFA ( kcat of 0.752 × 10 −3 and 0.217 × 10 −3 s −1, respectively) as compared to JH acid I (JHA I) ( cis/trans/cis ; 2 Z, 6 E, 10 cis ), JHA III (2 E, 6 E, 10cis ), and JHA I ( trans / cis / cis ; 2 E, 2 Z, 10 cis ) ( kcat of 0.081 × 10 −3, 0.013 × 10 −3, and 0.003 × 10 −3 s −1, respectively). This suggests that this ortholog is a Dc FA‐o‐methyl transferase gene ( fmt D), not a jmt D, and that JH biosynthesis in D. citri proceeds from FA to JH III through methyl farnesoate (MF). Dc FA‐o‐MT does not require Ca 2+, Mg 2+ or Zn 2+, however, Zn 2+ (1 mM) completely inhibits the enzyme probably by binding H115 at the active groove. This represents the first purified FA‐o‐MT from Hemiptera with preferred biological activity for FA and not JHA. Abstract : A putative JH acid methyltransferase ortholog gene ( jmtD ) and its cognate cDNA were identified in D. citri . This gene is expressed in all life stages in D. citri . The purified enzyme expressed from cDNA in E. coli showed high preference for farnesoic acid (FA) and homoFA. This suggests that this ortholog is a Dc FA‐o‐methyl transferase gene ( fmt D), and not jmt D. First purified FA‐o‐MT from any insect order with preferred biological activity for FA and not JHA.